The Correlation between the Weight of Ovary, Number of Follicles, and Quality of Oocytes of Culling Female Bovine in Slaughterhouse - Chandramohan, Koshini; Utama, Suzanita; Lestari, Tita Damayanti; Rimayanti; Safitri, Erma; Hestianah, Eka Pramyrtha; Mulyati, Sri; Damayanti, Ratna; Khairullah, Aswin Rafif; Hasib, Abdullah (Media Kedokteran Hewan, 2024)
The purpose of this research was to determine the correlation between the weight of the ovary, the number of follicles, and the quality of the oocytes from the culling female bovine   obtained from the slaughterhouse. The variation may affect the potential of the ovary to produce follicles. Paired ovaries were obtained from female bovines.  Follicle numbers were recorded and divided into three size categories (small: 3 mm, medium: < 3 mm-8 mm, and large: > 8 mm). Oocytes were aspirated and the number of oocytes was recorded and graded into four categories (grades A, B, C, and D). There was a positive correlation between the weight of the ovary and the number of follicles, which is 0.560 with the regression equation y = 3.52 + 0.501 x. There was a positive correlation between the number of follicles and the number of oocytes, which is 0.546 with the regression equation y =2.48 + 1.204 x. There was a positive correlation between the number of oocytes and the grade of oocytes, which is 0.520, with the regression equation y = 0.93 + 0.800 x. There was no correlation between the weight of the ovary and oocyte grade A, which is 0.013.